Ratio of serum proBDNF to BDNF and its association with cognitive performance and brain morphometry in mild cognitive impairment: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Cechova, Katerina; Angelucci, Francesco; Markova, Hana; Nikolai, Tomas; Matuskova, Veronika; Laczó, Jan; Nedelska, Zuzana; Vyhnalek, Martin; Hort, Jakub
Abstract: Background: Brain‐derived neurotrophic factor (BDNF) is the neurotrophin well‐known for its role in neurogenesis, synaptic plasticity and enhancement of long‐term potentiation (LTP). Its precursor proBDNF exhibits opposite biological function – inhibits LTP and increases long‐term depression (LTD) in the brain. Altered proBDNF/BDNF ratio in favor of the pro‐form may lead to enhancement of LTD and reduction of LTP in hippocampal neurons with consequent synaptic dysfunction and memory deficits. To explore this hypothesis, we investigated the associations of serum proBDNF, mature BDNF and its ratio (proBDNF/BDNF) with cognitive performance and structural changes of AD‐related brain regions in individuals with amnestic mild cognitive impairment (aMCI). Method: 95 individuals with aMCI (age = 68.5 ± 7.3; MMSE = 26.1 ± 2.4) were recruited from the Czech Brain Aging Study. All participants underwent clinical and laboratory evaluation (with APOE and BDNF genotyping), comprehensive neuropsychological examination and brain MRI (1.5T). FreeSurfer 5.3 software was used to measure left and right hippocampal volume and left and right entorhinal and parahippocampal thickness. Serum levels of proBDNF and BDNF were measured by sandwich enzyme‐linked immunosorbent assay (ELISA). Result: A negative correlation was found between serum proBDNF/BDNF ratio and verbal memory (r = ‐0. 25, p = 0.04) and executive function (r = ‐0. 30, p = 0.02) but not with other cognitive composite scores (ps > 0.26). A trend of positive correlation was found between serum BDNF levels and verbal memory domain (r = 0.23, p = 0.08). No other correlation between BDNF and proBDNF levels and cognitive performance was significant. Correlations of proBDNF and BDNF levels and its ratio with volume and thickness of AD‐related brain regions were not significant. Conclusion: Higher proBDNF/BDNF ratio is associated with lower cognitive performance in verbal memory and executive function but not with structural brain changes in aMCI individuals. Our findings suggest that proBDNF/BDNF ratio may be a more reliable blood biomarker of cognitive change than BDNF and proBDNF levels alone.